1999
DOI: 10.1046/j.1365-2923.1999.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Problem‐based learning versus lecture‐based learning in a course of basic pharmacology: a controlled, randomized study

Abstract: Since its first implementation in a medical programme at McMaster University, Canada, problem-based learning (PBL) has become a well-established means of teaching and learning medicine. Extensive research has been conducted and a number of strengths of the method are well supported. Several items, however, remain unclear although there is evidence that no relevant difference exists in factual knowledge among students from PBL and traditional curricula, a controlled, randomized study has not been conducted to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
122
4
9

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(141 citation statements)
references
References 11 publications
6
122
4
9
Order By: Relevance
“…1). This result is not consistent with some previous reports [11,13]. Since our university is a military medical school, all of the students are soldiers, and biochemistry is one of their basic medical training requirements, this may result in high participation.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…1). This result is not consistent with some previous reports [11,13]. Since our university is a military medical school, all of the students are soldiers, and biochemistry is one of their basic medical training requirements, this may result in high participation.…”
Section: Discussioncontrasting
confidence: 93%
“…The PBL students achieved better results in the categories of short-essay questions and case-analysis questions while no difference in the multiple-choice questions, which is consistent with Wolfram's results [11]. This fact indicates that examination testing of more complex levels of knowledge, (i.e.…”
Section: Discussionsupporting
confidence: 86%
“…Some previous studies have reported that certain teaching-learning methods, such as problem based learning, are favoured over the traditional methods i.e. lectures [15,16]. However, only little is known on whether the learning style of a student affects his/her preference for a specific teaching strategy/instructional method.…”
Section: Resultsmentioning
confidence: 99%
“…PBL has since been adopted by other medical schools and adapted by other disciplines leading to an assortment of learning and teaching models. Studies indicate that students prefer PBL to traditional lecture formats [2][3][4][5]. Numerous studies indicate that the process of learning is different in PBL and PBL challenges students to become self-directed life learners [2,3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that students prefer PBL to traditional lecture formats [2][3][4][5]. Numerous studies indicate that the process of learning is different in PBL and PBL challenges students to become self-directed life learners [2,3,6]. Few studies have demonstrated the effectiveness of PBL in an undergraduate nursing program on student test performance.…”
Section: Introductionmentioning
confidence: 99%